IQ Test Expert System for Selecting Candidates for New Students - Arrosty, Mawaddah; Sagala, Jijon Raphita (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
The IQ test information system at the Taman Siswa Lubukpakam Private High School is still done by selling, after the which Recapitulation is done manually, the obstacle is that the school has Difficulties in delivering information on the results of IQ tests that are slow and not timely , and in the calculation of the IQ test results that require a long time, the resulting in slow work.The making of this system uses the methodology of field researchers, interviews and observations. This requires some Data Including student data. Data Reviews These are expected to be the basis of making this application system in order to present the required information quickly intervening and accurately. IQ tests in the determination and consideration of class Unmatched in schools are usually done manually and the make enough time to find out the IQ results in Determining prospective new students at school, besides calculating the IQ test results Because it is quite complicated, then to Facilitate the school in carrying out the IQ test to Determine the prospective new students required the existence of a computer-based application and to build applications that will be used by the web programming language. The results of the evaluation of the application that was built were very helpful and accelerated the school in Determining the selection of classrooms that adjusted Reviews their abilities and civilized the use of computers among students. then to Facilitate the school in carrying out the IQ Test to Determine the prospective new students required the existence of a computer-based application and to build applications that will be used by the Web programming language. The results of the evaluation of the application that was built were very helpful and accelerated the school in Determining the selection of classrooms that adjusted Reviews their abilities and civilized the use of computers among students. then to Facilitate the school in carrying out the IQ Test to Determine the prospective new students required the existence of a computer-based application and to build applications that will be used by the Web programming language. The results of the evaluation of the application that was built were very helpful and accelerated the school in Determining the selection of classrooms that adjusted Reviews their abilities and civilized the use of computers among students